El uso del catálogo automatizado en la biblioteca del colegio “padre miguel gamboa” de la parroquia Puerto Francisco de Orellana, provincia de Orellana y su incidencia en la calidad del servicio de circulación y préstamo a los docentes y estudiantes. Periodo 2013-2014 - Enríquez Bergara, María de Lourdes (2014)
The present study titled: THE USE OF AUTOMATED CATALOGUE IN THE “PADRE MIGUEL GAMBOA” SCHOOL LIBRARY PUERTO FRANCISCO DE ORELLANA PARISH, ORELLANA PROVINCE AND ITS IMPACT ON THE QUALITY SERVICE OF MOVEMENT AND LOAN TO TEACHERS AND STUDENTS. PERIOD 2013-2014, it is structured and developed in accordance with the regulations of the Loja National University. The general objective was raised: Contribute to the management of the College Fiscomisional “Padre Miguel Gamboa“ identifying areas for improvement of services that allow Circulation and Loan satisfaction library users. The methods that use was made were: Scientific , Deductive , Analytical , Descriptive , Statistical Model , the same that were used to describe and explain the shape and the relationship between the Automated Catalogs and Service Quality of Movement and Loan to teachers and students " Padre Miguel Gamboa" School Puerto Francisco de Orellana Parish. As research techniques were applied two surveys: Teachers and Students to establish the incidence between the use of automated catalogs and service quality Circulation and Loan, and, to management and librarian to determine the degree of satisfaction users of the library service in relation to the Loans and Circulation, period 2013-2014. According to the results of the survey of Teachers and Students to establish the incidence between the use of automated catalogs and service quality and Loan Outstanding teachers and students, it is determined that 87% of teachers and 71% of students say Automated Catalogue allow to provide a service more efficient circulation and Loan; 29% of students and 13% of teachers say no. The results of the survey to managers and librarians to determine the degree of satisfaction of library users regarding the service of Circulation and Loan provides that 60 % believe that teachers via the Service and Loan and Circulation SI students meet their needs for study and research, 20% considers that sometimes, 20% say no